Nefropatía mesoamericana: revisión breve basada en el segundo taller del Consorcio para el estudio de la Epidemia de Nefropatía en Centroamérica y México (CENCAM) - García-Trabanino, Ramón (2016)
Mesoamerican nephropathy (MeN) is a form of endemic chronic kidney disease (CKD) unrelated to diabetes or hypertension and its causes are still undetermined. Clinically, patients with MeN have no or only mild proteinuria and mild or absent systemic hypertension. MeN is highly prevalent and with elevated mortality in the Pacific coast of Central America. The Consortium for the Study of the Epidemic of Nephropathy in Central America and Mexico (CENCAM) held a workshop in San José, Costa Rica to review all available scientific evidence, identify knowledge gaps, and propose recommendations. The purpose of this review is to present a brief summary of the update on the current evidence evaluated during the workshop, which is available in the full Scientific Report. Although the aetiology is still not clear, there is consensus among most researchers that MeN has an important occupational and environmental component, and that physical exertion under heat stress is probably related to the disease. Continuous repetitive episodes of dehydration and heat stress may play an important role in the pathophysiology of the disease. It is likely that the cause of MeN is multifactorial, and other risk factors have been proposed that deserve to be studied in greater depth, including: exposure to some agrochemicals, some infectious agents (Leptospira and others), frequent use of analgesics, genetic susceptibility, and social determinants of health. MeN poses a historic challenge for Latin American nephrology, and its approach must be multi-sectoral.